Validation of the French Clinical Assessment Interview for Negative Symptoms in a Sample of Stable French Individuals With Schizophrenia - Laraki, Yasmine; Lebrun, Cindy; Merenciano, Marine; Eisenblaetter, Margot; Attal, Jerôme; Macgregor, Alexandra; Decombe, Amandine; Capdevielle, Delphine; Raffard, Stéphane (Frontiers in Psychiatry, 2022)
Objectives: The Clinical Assessment Interview for Negative Symptoms is an interview-based instrument evaluating the existence and severity of negative symptoms in people diagnosed with schizophrenia or schizoaffective disorder. The aim of this study is to translate and validate a French version of the CAINS in a French sample of outpatients diagnosed with schizophrenia or schizoaffective disorder. Method: In this study, we included 84 outpatients with a diagnosis of schizophrenia from the University Department of Adult Psychiatry in Montpellier, France. All participants were assessed for the severity of negative symptoms as well as level of depression. Psychometric properties of the French CAINS were investigated including its factor structure, internal consistency, and inter-rater and test-retest reliabilities. We also determined the discriminant and convergent validity. Results: Exploratory factor analysis and parallel analysis reproduced the 2-factor model, and explained 43.55% of the total score variation with good internal consistency (Cronbach α of 0.87). Both inter-rater and test-retest reliabilities were high for the CAINS and its subscales (intraclass correlation coefficient range, 0.89 to 0.99). The standard errors of measurement and minimal detectable change were also investigated. Convergent validity of the CAINS was underpinned by correlations obtained with various measures of negative symptoms. Adequate discriminant validity was established by showing that the CAINS did not correlate with positive symptoms. Conclusions: Overall, our results obtained were similar to those found in the original study of the CAINS. Structural analyses also replicated the two-factor model of the CAINS. Our results indicate that the French CAINS has robust psychometric properties and is a valid tool for evaluating negative symptoms in French speaking individuals diagnosed with schizophrenia.